2003
DOI: 10.1590/s1517-74912003000400003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of low-level laser therapy on biomodulation of collagen and elastic fibers

Abstract: The study of low-level laser therapy upon extracellular matrix elements is important to understand the wound healing process under this agent. However, little is known about the interference of laser light in relation to collagen and elastic fibers. Cutaneous wounds were performed on the back of 72 Wistar rats and a Ga-Al-As low-level laser was punctually applied with different energy densities. The animals were killed after 24, 48, 72 hours and 5, 7 and 14 days. Tissues were stained with hematoxilin-eosin, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
2
29

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 12 publications
7
67
2
29
Order By: Relevance
“…According to Medrado et al (14) and Pugliese et al (15), the use of GaAlAs laser at lower energy densities had a significant effect on the cicatrization of tissues, accelerating tissue repair through decreased edema, improved granulation tissue and fibroblast proliferation stimulation. In contrast to our results, they showed that 4 J/cm 2 laser is less effective for early wound closure during every experiment (15). According to Enwemeka et al (9) and Woodruff et al (16), the use of 632.8 and 780 nm laser therapy positively influences several tissue repair parameters, including reduced wound area and healing time, while the best energy density results range between 19 and 24 J/cm 2 and densities below 8.25 J/cm 2 and above 130 J/ cm 2 do not produce good wound closure results.…”
Section: Discussioncontrasting
confidence: 99%
“…According to Medrado et al (14) and Pugliese et al (15), the use of GaAlAs laser at lower energy densities had a significant effect on the cicatrization of tissues, accelerating tissue repair through decreased edema, improved granulation tissue and fibroblast proliferation stimulation. In contrast to our results, they showed that 4 J/cm 2 laser is less effective for early wound closure during every experiment (15). According to Enwemeka et al (9) and Woodruff et al (16), the use of 632.8 and 780 nm laser therapy positively influences several tissue repair parameters, including reduced wound area and healing time, while the best energy density results range between 19 and 24 J/cm 2 and densities below 8.25 J/cm 2 and above 130 J/ cm 2 do not produce good wound closure results.…”
Section: Discussioncontrasting
confidence: 99%
“…It is noteworthy that the predominance of type III collagen, provides a fragile scar on your tension, but on the other hand, excess type I collagen is responsible for a healing of poor quality, showing hypertrophic appearance. Notwithstanding increased collagen synthesis is considered a good marker of healing evolution, over deposition of these fibers within the wound area may provoke excessive accumulation of scar tissue, resulting in hypertrophic scars or keloids 18 . However, this undesirable effect can be minimized by applying correct dosages of Laser irradiation in order avoid over stimulation of fibroblastic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, Pugliese et al 17 observed the influences of the GaAlAs laser on the biomodulation of elastic fibers and collagen in skin wounds in rats, concluding that 4 J/cm 2 was superior to 8 J/cm 2 . However, neither their study nor that of Matera et al 4 stated the parameters needed to arrive at the final energy, although Matera pointed out the importance of giving details about the dose.…”
Section: Resultsmentioning
confidence: 77%